Relationship between Family Function, Anxiety, and Quality of Life for Older Adults with Hypertension in Low-Income Communities - Meng Zhang; Wenyan Zhang; Yu Liu; Meiliyang Wu; Jin Zhou; Zhongmin Mao (International Journal of Hypertension)
Background. Effective functional family was beneficial for older adults’ health, which may affect the quality of life (QoL) in hypertension patients. This study aimed to clarify the association between family function, anxiety, and QoL for older adults with hypertension in low-income communities. Methods. A questionnaire survey was conducted on 363 older adults with hypertension in low-income communities in Wuhan from September 2019 to November 2019. The relationships among the variables were examined by Pearson’s correlation analysis. Predictor effects were tested using hierarchical multiple regressions, controlling for demographic characteristics. The structural equation model (SEM) was used to test the mediation effects of anxiety on the pathway from family function to QoL. Results. Family function was negatively correlated with the self-rating anxiety scale (SAS) score and positively correlated with the mental component score (MCS), but had no influence on the physical component score (PCS). Both PCS and MCS were negatively correlated with SAS. Anxiety was the negative predictor of MCS and PCS. Family function was the positive predictor of MCS, but had no influence on PCS. The path model indicated that anxiety significantly mediated the link between family function and QoL (R2 = 32.8%), but only partially. Conclusion. A significant correlation between anxiety, family function, and QoL was found. Anxiety had a partial mediating effect on the relationship between family function and QoL. Further research should focus on increasing the level of family function and reducing the perceived anxiety of older adults with hypertension to improve their QoL level.